Charting the transient universe using radio continuum surveys - Macquart, Jean-Pierre (2015)
The field of radio transients is exploding with the discovery of diverse new phenomena fuelled by recent advances in telescope and computational capabilities. The desire to maximise time on sky to detect ever more and rarer events drives us to share telescope time with large continuum surveys. We discuss here the advantages of a symbiotic relationship between transients and continuum surveys, and show how an understanding of the time domain can constitute an important facet of continuum survey data with regard to quality control, the interpretation of flux density and spectral information, and the origin of the radio emission. One example at centimetre wavelengths is the presence of intra-day variability, which sifts for the presence of 1-100µas structure and potentially serves as a discriminant of AGN and starburst-related radio emission. We identify and discuss four main issues for the successful integration of transients and continuum surveys.